2011
DOI: 10.1542/neo.12-9-e517
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in the Small Intestine of the Preterm Infant

Abstract: The gastrointestinal tract comprises the largest surface area of the human body. This area is constantly exposed to myriad antigens as well as the large number of bacteria that coexist in the intestinal lumen. To protect against this exposure and help distinguish “self ” from “foreign,” the intestinal tract has evolved a sophisticated barrier defense system that includes both innate and adaptive immune systems. However, infants who are born preterm do not have the benefit of an adequate immune response and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 72 publications
2
78
0
Order By: Relevance
“…We (26,27) and others (20,41,53) have shown the dysregulation of inflammatory cytokines in the intestinal mucosa during NEC pathogenesis. Par-ticularly, interleukin (IL)-6, IL-8, IL-12, IL-18, and tumor necrosis factor-␣ (TNF-␣) have an important role and a diagnostic value in sepsis and in NEC (9,26,45).…”
mentioning
confidence: 82%
“…We (26,27) and others (20,41,53) have shown the dysregulation of inflammatory cytokines in the intestinal mucosa during NEC pathogenesis. Par-ticularly, interleukin (IL)-6, IL-8, IL-12, IL-18, and tumor necrosis factor-␣ (TNF-␣) have an important role and a diagnostic value in sepsis and in NEC (9,26,45).…”
mentioning
confidence: 82%
“…A recent systematic review and meta-analysis of available studies concluded that chorioamnionitis increases the risk of NEC [53]. Differences in the immune response to mucosal damage and the microbiota may also be responsible for the exaggerated inflammatory response in NEC [54]. Recent studies have highlighted such differences, such as those showing that intraepithelial T cell receptor γδ lymphocytes are decreased in surgical NEC specimens compared with appropriate controls [55], as are lamina propria T regulatory cells [56].…”
Section: Pathogenesismentioning
confidence: 99%
“…These authors reported that the time-limit for NEC induction in mice is 14-21 d, most likely due to the increasing development of the gut (36). Up to this, age the maturity of the bowel in rodents has been shown to correspond to the maturity of a human preterm neonate (37,38).…”
Section: Articlesmentioning
confidence: 99%